2020
DOI: 10.1002/ase.1996
|View full text |Cite
|
Sign up to set email alerts
|

Clay‐Based Modeling in the Anatomist's Toolkit: A Systematic Review

Abstract: Anatomical education has suffered from reduced teaching time and poor availability of staff and resources over the past thirty years. Clay-based modeling (CBM) is an alternative technique for teaching anatomy that can improve student knowledge and experience. This systematic review aimed to summarize and appraise the quality of the literature describing the uses, advantages, and limitations of CBM compared to alternative methods of teaching human gross anatomy to students or qualified healthcare professionals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…Over the last decades, alternative and less costly teaching technologies (3D printing, the use of virtual reality, and dissection software programs) have gradually replaced traditional anatomical education, with multiple ranges of study modules based on curricular integration (Nicholson et al, 2006; Wilson et al, 2018; Curlewis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, alternative and less costly teaching technologies (3D printing, the use of virtual reality, and dissection software programs) have gradually replaced traditional anatomical education, with multiple ranges of study modules based on curricular integration (Nicholson et al, 2006; Wilson et al, 2018; Curlewis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is impossible to explore changes in learning provision in anatomy over the last 20 years without considering the rise of innovation, including both the rise of arts and humanities, for example, body painting (Finn & McLachlan, 2010 ), clay modeling (Oh et al, 2009 ; Bareither et al, 2013 ; Curlewis et al, 2021 ), and also technology. Globally, there has been an explosion in the use of TEL and the use of personal electronic devices (Swedin & Ferro, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown its benefits in enhancing understanding and engaging students, but its effectiveness depends on the implementation and student preferences [18][19][20] (Kooloos et al, 2014;Curlewis et al, 2020). 21,22 To investigate this, we will conduct a comparative study examining the differences in students' geometrical mental representations formed through verbal descriptions alone and those enhanced after a tactile interaction. This comparison will enable us to objectively observe the development and accuracy of mental representations, thereby evaluating the reliability of clay modeling as an assessment tool.…”
Section: Introductionmentioning
confidence: 99%